(2+√2)la a doua-(2√2-3)la a doua
Răspunsuri la întrebare
Răspuns de
0
Metoda1 :=(2+rad2-2rad2+3)(2+rad2+2rad2-3)=(5-rad2)(3rad2 - 1)= 15rad2 - 5 - 3x2 + rad2 = 16rad2 - 11, am folosit a^2 - b^2 = (a-b)(a+b)
------------------------------------------------------------------------------------
Metoda2: 4+4rad2 + 2 - 8+ 12rad2 -9 = 16rad2 - 11, am folosit (a+/-b)^2 = a^2 +/- 2ab +b^2
---------------------------------------------
Succes in continuare!
------------------------------------------------------------------------------------
Metoda2: 4+4rad2 + 2 - 8+ 12rad2 -9 = 16rad2 - 11, am folosit (a+/-b)^2 = a^2 +/- 2ab +b^2
---------------------------------------------
Succes in continuare!
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă